Equivalence of Differential Operators in Spaces of Analytic Functions over the Tate Field - Volchkov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain conditions for the equivalence of certain differential operators in spaces of analytic functions over the Tate field.